Silver-catalyzed direct Csp2-H radical phosphorylation of coumarins with H-phosphites. Issue 42 (21st October 2015) - Yuan, Jin-Wei; Li, Yuan-Zhe; Yang, Liang-Ru; Mai, Wen-Peng; Mao, Pu; Xiao, Yong-Mei; Qu, Ling-Bo
Abstract: AgNO3 -catalyzed direct Csp2 -H radical phosphorylation of coumarins with H -phosphites to afford selective coumarin-3-yl phosphonate in moderate to good yields is described. This method can be also applied to the phosphorylation of quinolinones. Graphical abstract: